2018
DOI: 10.1186/s13550-018-0463-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow cell homing to sites of acute tibial fracture: 89Zr-oxine cell labeling with positron emission tomographic imaging in a mouse model

Abstract: BackgroundBone fracture healing is dependent upon the rapid migration and engraftment of bone marrow (BM) progenitor and stem cells to the site of injury. Stromal cell-derived factor-1 plays a crucial role in recruiting BM cells expressing its receptor CXCR4. Recently, a CXCR4 antagonist, plerixafor, has been used to mobilize BM cells into the blood in efforts to enhance cell migration to sites of injury presumably improving healing. In this study, we employed zirconium-89 (89Zr)-oxine-labeled BM cells imaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
(45 reference statements)
4
25
0
Order By: Relevance
“…With the introduction of total-body clinical PET scanners, this is set to increase by a further~40fold, reducing scan times and radioactive doses for patients and thus increasing the practicality of whole-body cell tracking in the clinic [19]. A handful of preclinical studies have so far shown the worth of 89 Zr-oxine in tracking cell therapies in mouse models, including T cells [20,21], dendritic cells, NK cells [17], and bone marrow cells [22,23]. However, 89 Zr-oxine toxicity is dependent on the amount used for labelling and varies between cell types, requiring individual evaluation with each prospective cell therapy prior to clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of total-body clinical PET scanners, this is set to increase by a further~40fold, reducing scan times and radioactive doses for patients and thus increasing the practicality of whole-body cell tracking in the clinic [19]. A handful of preclinical studies have so far shown the worth of 89 Zr-oxine in tracking cell therapies in mouse models, including T cells [20,21], dendritic cells, NK cells [17], and bone marrow cells [22,23]. However, 89 Zr-oxine toxicity is dependent on the amount used for labelling and varies between cell types, requiring individual evaluation with each prospective cell therapy prior to clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In a bone fracture model, 89 Zr-oxine PET further shows the mobilization of pre-transferred 89 Zr-labeled bone marrow cells from pre-distributed organs (bone marrow, spleen, and liver) to a site of fracture within 1 day of injury [63]. This re-distribution of pre-distributed bone marrow cells is also impaired by plerixafor treatment [63]. These reports indicate that 89 Zr-oxine labeling of highly radiosensitive bone marrow could be performed with minimum effect on functionality of the cells.…”
Section: Monitoring Of Transferred Cells Using 89 Zr-oxine Pet In Moumentioning
confidence: 96%
“… 42 Adiponectin directly 40 and through increasing S1P in the serum, 17 leads to increased osteoblast progenitor migration into the circulation and to bone in health, 48 which is enhanced during injury. 41 , 116 , 117 In contrast, S1P chemorepels osteoclast progenitors and osteoclasts, 51 leading to decreased migration to damaged sites. This ultimately maintains the balance between resorption (red) and formation (green) to ensure structured bone repair …”
Section: Regulator Of Osteoblast and Osteoclast Progenitor Migrationmentioning
confidence: 99%